Characteristics of Public Health Registered Nurses and Advanced Practice Registered Nurses: Lessons Learned From the 2018 National Sample Survey of Registered Nurses. (May 2023) - Choi, Yongjin; Armstrong, David P.; Moore, Jean
Objectives: Little research has compared the demographic and practice characteristics of registered nurses (RNs) who work in public health (PH RNs) with other RNs and advanced practice registered nurses (APRNs) who work in public health (PH APRNs) with other APRNs. We examined differences in characteristics between PH RNs and other RNs and between PH APRNs and other APRNs. Methods: Using the 2018 National Sample Survey of Registered Nurses (N = 43 960), we examined demographic and practice characteristics, training needs, job satisfaction, and wages of PH RNs compared with other RNs and PH APRNs compared with other APRNs. We used independent sample t tests to determine significant differences between PH RNs and other RNs and between PH APRNs and other APRNs. Results: On average, PH RNs and PH APRNs earned significantly less than other RNs (7082 difference) and APRNs (16 362 difference) (both P < .001). However, their job satisfaction was comparable. PH RNs and PH APRNs were also significantly more likely than other RNs and APRNs to report the need for more training in social determinants of health (20 [ P < .001] and 9 [ P = .04] percentage points higher, respectively), working in medically underserved communities (25 and 23 percentage points higher, respectively [ P < .001 for both]), population-based health (23 and 20 percentage points higher, respectively [ P < .001 for both]), and mental health (13 and 8 percentage points higher, respectively [ P < .001 for both]). Conclusions: Efforts that expand public health infrastructure and workforce development must consider the value of a diverse public health nursing workforce to protect community health. Future studies should include more detailed analyses of PH RNs and PH APRNs and their roles.